Multifrequency seafloor acoustic backscatter as a tool for improved biological and geological assessments – updating knowledge, prospects, and challenges - Menandro, Pedro S.; Misiuk, Benjamin; Schneider von Deimling, Jens; Bastos, Alex C.; Brown, Craig J. (Frontiers in Remote Sensing, 2025)
Multibeam echosounders (MBES) have emerged as a primary tool for seafloor mapping over the past three decades. Technological advancements and improved data processing methods have increased the accuracy and spatial resolution of bathymetric measurements, and have also led to the increasing use of MBES backscatter data for seafloor geological and benthic habitat mapping applications. MBES backscatter is now frequently used to characterize habitat for marine flora and fauna, contribute to the development of effective marine spatial planning and management strategies, and generally better classify the seabed. Recently, further technological advances have enabled the acquisition and analysis of backscatter at multiple sonar operating frequencies (multifrequency backscatter), with follow-on potential benefits for improved seafloor characterization and classification. This review focuses on the currently available peer-reviewed papers related to multifrequency seafloor acoustic backscatter, providing a comprehensive summary of the contributions across different benthic environments, setting the stage for related applications and outlining challenges and research directions.